Characterization of bovine cellular and serum antibody responses during infection by Cryptosporidium parvum. - Whitmire, W M (1991)
Cellular and serum antibody responses of calves were monitored for 23 days after oral inoculation of the calves with oocysts of Cryptosporidium parvum. In vitro blastogenic responses of peripheral blood lymphocytes were assessed after stimulation with a C. parvum preparation. Specific lymphocyte blastogenic responses to the parasite were detected 2 days after inoculation. Parasite-specific antibody titers were demonstrable 7 days after inoculation with oocysts and achieved peak levels 9 days after inoculation, coinciding with oocyst shedding at 5 to 10 days after inoculation. Both lymphocyte and antibody responses remained elevated until the termination of the experiment. Immunoblotting the C. parvum preparation with serum from an infected calf revealed six major parasite antigens. Five of these antigens reacted on immunoblots from 7 to 14 days after inoculation with oocysts. A parasite antigen of approximately 11,000 molecular weight demonstrated intense reactivity on immunoblots from 7 to 23 days after inoculation. The 11,000-molecular-weight antigen also reacted on immunoblots with parenterally raised antioocyst and antisporozoite rabbit sera. These results indicate that cell-mediated as well as humoral immune responses are initiated by cryptosporidial infection in calves and that the 11,000-molecular-weight parasite antigen is immunodominant.